Front view of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The Undeshwar Temple follows a Saparatha (seven projections on all four sides) architectural plan and consists of a mukhamandapa (front porch), mandapa (pillared hall) with extensions on the north and south sides, an antarala (vestibule or antechamber), and garbhagriha (sanctum sanctorum).